Modulating the surface potential of microspheres by phase transition in strontium doped barium titanate to restore the electric microenvironment for bone regeneration - Wang, Peng; Zhou, Xiaosong; Lv, Caili; Wang, Yu; Wang, Zongliang; Wang, Liqiang; Zhu, Yongzhan; Guo, Min; Zhang, Peibiao (Frontiers in Bioengineering and Biotechnology, 2022)
The endogenous electrical potential generated by native bone and periosteum plays a key role in maintaining bone mass and quality. Inspired by the electrical properties of bone, different negative surface potentials are built on microspheres to restore electric microenvironment for powerful bone regeneration, which was prepared by the combination of strontium-doped barium titanate (Sr-BTO) nanoparticles and poly (lactic-co-glycolic acid) (PLGA) with high electrostatic voltage field (HEV). The surface potential was modulated through regulating the phase composition of nanoparticles in microspheres by the doping amount of strontium ion (Sr2+). As a result, the 0.1Sr-BTO/PLGA group shows the lowest surface potential and its relative permittivity is closer to natural bone. As expected, the 0.1Sr-BTO/PLGA microspheres performed cytocompatibility, osteogenic activity in vitro and enhance bone regeneration in vivo. Furthermore, the potential mechanism of Sr-BTO/PLGA microspheres to promote osteogenic differentiation was further explored. The lower surface potential generated on Sr-BTO/PLGA microspheres regulates cell membrane potential and leads to an increase in the intracellular calcium ion (Ca2+) concentration, which could activate the CaN/NFAT signaling pathway to promote osteogenic differentiation. This study established an effective method to modulate the surface potential, which provides a prospective exploration for electrical stimulation therapy. The 0.1Sr-BTO/PLGA microsphere with lower surface potential and bone-matched dielectric constant is expected to have great potential in the field of bone regeneration.